Extensão da marca Nutella: lançamento do snack Nutella & Go - Lopes, Vera Lídia Ventura (2020)
This project has as its main goal the development of a Marketing Plan at a strategic and operational level in order to support the launch of a brand extension of one of the well-known love brands in Portugal - Nutella, through a new snack. The product will be launched in the Portuguese market on February 5th of 2019, also considered as the Nutella day. In this project, we have identified the potential market and the value of this new Ferrero launch due to its functional elements that easily distinguish this snack from all the other players in the market. On the other hand, it is possible to refer that also external and internal analysis were carried on. These allowed us to better understand several impactful factors for the launch of this product, as the Nutella position in Portugal, the performance of Ferrero in the snacks segment, the crucial trends for a launch with these characteristics and the potential of new consumption occasions, as the on-the-go possibility. Having this into account, we have also developed an operational and strategic study, which allowed us to evaluate the performance that we expect from the Nutella & Go! in its first years of activity in the Portuguese market, as such the necessary resources to implement this project successively. In addition, it will be feasible to visualize a marketing plan and a marketing-mix that will allow us to create a snack that will meet the expectations of its young target. Finally, we have provided a set of relevant information related to the budget allocated to the project itself and also to the forecast that we estimate for the first 3 years of this new Ferrero snack in the market: Nutella & Go!.